Strontium titanate / boron nitride nanotube composite ceramic core block and preparation method and application thereof

Through the preparation of composite ceramic cores of strontium titanate and functionalized boron nitride nanotubes, the problems of ceramic performance degradation and poor dispersion of boron nitride at high temperatures are solved, efficient thermal conductivity and mechanical properties are achieved, and high power radioactivity is ensured. Efficient and safe use of isotope heat source batteries.

CN119118658AActive Publication Date: 2024-12-13THE 404 COMPANY LIMITED CHINA NAT NUCLEAR

Patent Information

Application Number
CN202411126833.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-13
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The performance of high-power radioactive isotope heat source battery pellets deteriorates in high temperature and irradiated environments, resulting in limited heat transfer efficiency and service life. The existing ceramic composite materials perform poorly at high temperatures, have poor boron nitride dispersion and excessive mass proportion. Large leads to volume increase.

Method used

The composite ceramic core of strontium titanate and boron nitride nanotubes is used to functionalize the boron nitride nanotubes through alkaline solution, and is uniformly dispersed in the strontium titanate slurry. It is prepared by wet stirring and discharge plasma sintering process. Nitrogen The mass percentage of boronide nanotubes is 0.1% to 3%, with an average diameter of 50 nm, a length of 10-20 μm, and a strontium titanate particle diameter of 200 nm.

Benefits of technology

It significantly improves the thermal conductivity and mechanical properties of ceramic core pellets, maintains the structural integrity of boron nitride nanotubes, avoids volume increase, enhances high-temperature oxidation resistance and radiation stability, and improves thermoelectric conversion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118658A_ABST
    Figure CN119118658A_ABST
Patent Text Reader

Abstract

The invention relates to a strontium titanate / boron nitride nanotube composite ceramic core block and a preparation method and application thereof, the composite ceramic core block is prepared from strontium titanate and boron nitride nanotubes, and the mass percent of the boron nitride nanotubes in the strontium titanate / boron nitride nanotube composite ceramic core block is 0.1-3%. The preparation method comprises the following steps: slowly adding obtained surface modified boron nitride nanotube slurry into strontium titanate slurry to obtain strontium titanate / boron nitride nanotube slurry; heating and stirring the strontium titanate / boron nitride nanotube slurry to obtain strontium titanate / boron nitride nanotube composite powder; the strontium titanate / boron nitride nanotube composite powder is subjected to pellet blank compression molding and sintering, and the strontium titanate / boron nitride nanotube composite ceramic pellet is obtained. Compared with the prior art, the heat conduction and mechanical properties of the 90SrTiO3 ceramic core block can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite ceramic preparation, in particular to a strontium titanate / boron nitride nanotube composite ceramic core block and a preparation method and application thereof. Background Art

[0002] Radionuclides extracted from high-level liquid waste 90 Sr can be used to prepare isotope heat source batteries, the main component of which is strontium titanate ( 90 SrTiO3) ceramics. The harsh environment of high temperature and strong radiation faced by high-power radioisotope heat source batteries during long-term service will cause core block radiation damage, degradation of physical and mechanical properties and structural stability, thereby limiting its heat transfer efficiency and service life, seriously restricting the development of high-power radioisotope heat source batteries. How to effectively improve 90 The high temperature resistance, thermal conductivity, mechanical and radiation resistance of SrTiO3 ceramic core blocks ensure the efficient and safe use of high-power radioisotope heat source batteries, which is a very important issue at present.

[0003] The existing technology for enhancing the performance of ceramic materials mainly introduces a secondary strengthening phase into a single ceramic to prepare a composite ceramic. There is a technical document (Preparation and Performance Research of Strontium Titanate-based Thermoelectric Composite Materials [D]. Donghua University, 2022) that discloses a method for preparing a carbon nanotube (CNT) and strontium titanate (SrTiO3) ceramic composite material. The method is to composite CNT and SrTiO3 by heterogeneous deposition and then use discharge plasma sintering. The disadvantage is that at high temperatures, the carbon in the CNT will react with the oxygen in the SrTiO3 lattice. Therefore, when the high-power radioisotope heat source battery core block is in service for a long time under high temperature conditions, the structure of the CNT will be damaged by oxygen, resulting in the CNT strengthening technology being used for 90 The reinforcing properties of the SrTiO3 ceramic core block deteriorate, affecting the service life and performance of the nuclear battery.

[0004] There are technical documents ( 90 Design simulation and radiation optimization of Sr isotope battery radiation source [J]. Isotopes, 2024, 37(1): 49-54.), discloses a composite ceramic core block in which one-tenth of the mass of boron nitride powder is added to the strontium titanate powder ingredients. According to experiments, the thermal resistance of the core block is significantly reduced after adding boron nitride, which has a positive effect on improving the thermoelectric conversion performance of the battery. However, this method shows that the dispersion of boron nitride is poor, which reduces the strengthening effect of boron nitride on strontium titanate ceramics. In addition, the mass proportion of boron nitride in the technical literature is too large, which greatly increases the volume of the core block. Summary of the invention

[0005] The purpose of the present invention is to provide a strontium titanate / boron nitride nanotube composite ceramic core block and its preparation method and application, which can effectively improve 90 Thermal conductivity and mechanical properties of SrTiO3 ceramic pellets.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] On the one hand, the present invention provides a strontium titanate / boron nitride nanotube composite ceramic core block, which is prepared using strontium titanate and boron nitride nanotubes, and the mass percentage of boron nitride nanotubes in the strontium titanate / boron nitride nanotube composite ceramic core block is 0.1% to 3%.

[0008] Preferably, the boron nitride nanotubes have an average diameter of 50 nm and a length of 10-20 μm, and the strontium titanate has an average particle size of 200 nm.

[0009] In a second aspect, the present invention further provides a method for preparing the above-mentioned strontium titanate / boron nitride nanotube composite ceramic core block, comprising the following steps:

[0010] S1: functionalizing the boron nitride nanotubes with an alkaline solution to obtain surface-modified boron nitride nanotubes;

[0011] S2: Dispersing strontium titanate uniformly in anhydrous ethanol to obtain strontium titanate slurry, and stirring continuously;

[0012] S3: evenly dispersing the surface-modified boron nitride nanotubes in anhydrous ethanol to obtain a surface-modified boron nitride nanotube slurry, and adding the slurry to the strontium titanate slurry to obtain a strontium titanate / boron nitride nanotube slurry, and continuously stirring;

[0013] S4: heating and stirring the strontium titanate / boron nitride nanotube slurry to obtain a strontium titanate / boron nitride nanotube composite powder;

[0014] S5: pressing and sintering the strontium titanate / boron nitride nanotube composite powder into a core block embryo to obtain a strontium titanate / boron nitride nanotube composite ceramic core block.

[0015] Preferably, in step S1, the alkaline solution comprises a sodium hydroxide solution, the concentration of the sodium hydroxide is 5-6 mol / L, and the dosage ratio of the boron nitride nanotubes to the sodium hydroxide solution is (10-100 mg):15 mL.

[0016] Further preferably, in step S1, the specific process of the functionalization is: ultrasonically disperse the boron nitride nanotubes in a sodium hydroxide solution, place them in a polytetrafluoroethylene-lined hydrothermal reactor, react at a temperature of 110-180°C for 12-24 hours, centrifuge and wash until neutral, and dry at 70-90°C for 12-24 hours. Step S1 functionalizes the boron nitride nanotubes using a sodium hydroxide solution under high temperature and high pressure conditions in a reactor, so that the boron atoms on the surface of the boron nitride nanotubes are bonded to hydroxyl groups, thereby obtaining surface-modified boron nitride nanotubes.

[0017] Further preferably, in step S1, the specific process of the functionalization is: ultrasonically dispersing the boron nitride nanotubes in a sodium hydroxide solution, then placing them in a polytetrafluoroethylene-lined hydrothermal reactor, reacting them at a temperature of 110-180°C for 12-24 hours, taking them out and centrifugally filtering them with a centrifuge, washing the boron nitride nanotubes with deionized water until they are neutral, and then drying the boron nitride nanotubes in a drying oven at 80°C to obtain the modified boron nitride nanotubes.

[0018] Preferably, in step S2, the stirring is performed by an overhead electric stirrer at a stirring speed of 300 to 1200 rpm. The overhead electric stirrer can fully mix the strontium titanate and boron nitride nanotube slurry to ensure that the two will not be separated during the wet mixing process.

[0019] Further preferably, in step S2, strontium titanate powder is placed in a beaker, anhydrous ethanol is added for ultrasonic dispersion, and then the strontium titanate slurry is transferred to another large beaker and continuously stirred with an overhead electric stirrer.

[0020] Preferably, in step S3, the dispersion includes ultrasonic dispersion, the ultrasonic dispersion time is 2-3 hours, and during the ultrasonic dispersion, the temperature of the surface-modified boron nitride nanotube slurry is not higher than 60°C.

[0021] Preferably, in step S3, the surface-modified boron nitride nanotube slurry is dripped into the strontium titanate slurry at a rate of 1-5 ml per second.

[0022] Further preferably, in step S3, the surface-modified boron nitride nanotube slurry is dripped into the strontium titanate slurry using a pipette.

[0023] Preferably, in step S4, the heating and stirring is performed until the solvent in the strontium titanate-boron nitride nanotube slurry is dried, and before the strontium titanate / boron nitride nanotube composite powder is obtained, the strontium titanate / boron nitride nanotube slurry mixed with the solvent is placed in a vacuum drying oven for further drying, and the drying temperature of the vacuum drying oven is 80-120°C, and the drying time is 20-30 hours.

[0024] Preferably, in step S5, the sintering method includes spark plasma sintering, the sintering temperature is 1050-1200°C, the sintering pressure is 80-100 MPa, and the sintering temperature is maintained for 3-5 minutes after reaching the sintering temperature; after the insulation is completed, the temperature is reduced to 700-900°C and the pressure is removed and maintained for 5-10 minutes.

[0025] In a third aspect, the present invention also provides an application of the above-mentioned strontium titanate / boron nitride nanotube composite ceramic core block, including application in a high-power radioisotope heat source battery core block.

[0026] Boron nitride nanotubes (BNNTs) have a similar structure to CNTs. In addition to having high thermal conductivity and excellent mechanical properties, they have better high-temperature oxidation resistance than CNTs. Moreover, light elements such as boron in BNNTs can effectively reduce the bremsstrahlung generated by the interaction between β particles and the core block matrix, thereby reducing the radiation dose of the heat source core block to the environment. Therefore, they can be used in the field of isotope heat source oxide ceramic core blocks in high-temperature oxidizing environments. To this end, the present invention provides a strontium titanate / boron nitride nanotube composite ceramic core block and a preparation method and application thereof.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The present invention uses SrTiO3 ceramic as the main body and constructs a BNNT network in the ceramic matrix, wherein BNNT with excellent mechanical properties and thermal conductivity is used as a reinforcing phase to improve the density and uniformity of the ceramic core block, and fully ensure the thermal conductivity and mechanical properties of the composite ceramic core block.

[0029] (2) BNNT has better thermochemical stability than CNT and can be used in harsh environments with high temperatures and chemical activity, so it has a better strengthening effect in high-power radioisotope heat source battery core blocks.

[0030] (3) In the process of preparing strontium titanate ceramic core blocks, the present invention improves the uniform dispersion of boron nitride nanotubes in strontium titanate ceramic powder by modifying the surface of boron nitride nanotubes with hydroxyl groups and using wet stirring and mixing technology, thereby maintaining the structural integrity of the boron nitride nanotubes.

[0031] (4) The present invention not only can disperse the boron nitride nanotubes well in the strontium titanate ceramic matrix through an improved wet mixing method, but also can avoid the damage of the boron nitride caused by ball milling. By using high-crystal quality boron nitride nanotubes with an optimized mass ratio, the thermal conductivity of the core block is further increased and the thermal resistance of the core block is reduced. Under the premise of ensuring that the volume of the heat source core block is not significantly increased, it has a more positive effect on improving the thermoelectric conversion performance of the battery.

[0032] (5) The preparation method and process conditions of the strontium titanate / boron nitride nanotube composite ceramic core block of the present invention are simple and easy to implement, which is conducive to popularization and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope photograph of a composite powder obtained by wet mixing of boron nitride nanotubes modified by hydrothermal reaction with sodium hydroxide solution and strontium titanate powder in Example 1;

[0034] Figure 2 A comparison chart of thermal conductivity of SrTiO3-1wt.% BNNT, SrTiO3-2wt.% BNNT, SrTiO3-3wt.% BNNT composite ceramic core blocks prepared in Examples 1-3 respectively and SrTiO3 single-phase ceramic core blocks prepared in the comparative example;

[0035] Figure 3 This is a hardness comparison chart of the SrTiO3-2wt.% BNNT composite ceramic core block prepared in Example 2 and the SrTiO3 single-phase ceramic core block prepared in the comparative example. DETAILED DESCRIPTION

[0036] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0037] The present invention provides a strontium titanate / boron nitride nanotube composite ceramic core block, wherein the composite ceramic core block is prepared by using strontium titanate and boron nitride nanotubes, wherein the mass percentage of boron nitride nanotubes in the strontium titanate / boron nitride nanotube composite ceramic core block is 0.1% to 3%. The boron nitride nanotubes have an average diameter of 50nm and a length of 10-20μm, and the average particle size of strontium titanate is 200nm.

[0038] The strontium titanate / boron nitride nanotube composite ceramic core block is prepared by the following method:

[0039] (1) ultrasonically dispersing boron nitride nanotubes in a 5-6 mol / L sodium hydroxide solution, wherein the amount ratio of the boron nitride nanotubes to the sodium hydroxide solution is (10-100 mg):15 mL; then placing the boron nitride nanotubes in a polytetrafluoroethylene-lined hydrothermal reactor, reacting at a temperature of 110-180° C. for 12-24 hours, taking out, centrifugally filtering with a centrifuge, washing the boron nitride nanotubes with deionized water until neutral, and then drying the boron nitride nanotubes in a drying oven at 70-90° C. for 12-24 hours, functionalizing the boron nitride nanotubes, bonding the boron atoms on the surface of the boron nitride nanotubes to hydroxyl groups, and obtaining surface-modified boron nitride nanotubes;

[0040] (2) SrTiO3 powder was placed in a beaker, anhydrous ethanol was added for ultrasonic dispersion, and then the SrTiO3 slurry was transferred to another large beaker and stirred continuously with an overhead electric stirrer;

[0041] (3) mixing the boron nitride nanotubes obtained in step (1) with anhydrous ethanol and ultrasonically dispersing them for 2-3 hours while maintaining the temperature not exceeding 60° C., slowly adding the boron nitride nanotube dispersion into the SrTiO 3 slurry in step (2) at a rate of 1-5 ml per second using a pipette, and continuing to stir and mix;

[0042] (4) heating the stirred SrTiO3-BNNT slurry until it is dried and then stopping stirring. Taking out the dried powder and placing it in a vacuum drying oven for further drying, the drying temperature of the vacuum drying oven is 80-120°C, and the drying time is 20-30 hours, to obtain SrTiO3-BNNT composite powder;

[0043] (5) The SrTiO3-BNNT composite powder prepared in step (4) is loaded into a mold to form a core block embryo, and the embryo is sintered in a spark plasma sintering furnace to obtain a SrTiO3-BNNT composite ceramic core block, wherein the sintering temperature is 1050-1200°C, the sintering pressure is 80-100 MPa, and the sintering temperature is maintained for 3-5 minutes after reaching the sintering temperature; after the insulation is completed, the temperature is reduced to 700-900°C and the pressure is removed and the insulation is maintained for 5-10 minutes to prepare a strontium titanate / boron nitride nanotube composite ceramic core block.

[0044] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0045] The boron nitride nanotubes and strontium titanate used in the following examples are both selected from Beijing Dekedaojin Technology Co., Ltd.

[0046] The following describes it in detail with reference to specific embodiments.

[0047] Example 1

[0048] (1) 0.1 g of boron nitride nanotubes and 15 ml of 5 mol / L sodium hydroxide solution were mixed in a beaker and subjected to ultrasonic treatment for 30 min to obtain a mixed solution.

[0049] (2) The mixed solution obtained in step (1) was placed in a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 120° C. for 24 hours. After the hydrothermal reaction was completed, the mixed solution was centrifuged at 8000 rpm and the boron nitride nanotubes were repeatedly washed with deionized water. The last washing was done with anhydrous ethanol. The mixed solution was then placed in an oven and dried at 80° C. for 24 hours to obtain surface-modified boron nitride nanotubes.

[0050] (3) 6 g of SrTiO3 powder was placed in a beaker, and after ultrasonic dispersion with anhydrous ethanol, the SrTiO3 slurry was immediately transferred to the beaker and stirred continuously with an overhead electric stirrer.

[0051] (4) The boron nitride nanotubes obtained in step (2) were evenly divided into two portions of 0.03 g each, placed in two beakers containing 150 ml of anhydrous ethanol and ultrasonically dispersed for 2 hours. During the ultrasonic dispersion process, ice bags were used to keep the water temperature below 60°C. The portions were then added to the stirred SrTiO3 slurry in step (3) using a plastic straw and continued to be stirred and mixed.

[0052] (5) The stirred SrTiO3-1wt.% BNNT slurry was heated on a heating table until it was dried and then the stirring was stopped. The powder dried on the heating table was taken out and placed in a vacuum drying oven for further drying overnight. The drying temperature of the drying oven was 90°C.

[0053] (6) The SrTiO3-1wt.% BNNT composite powder prepared in step (5) is loaded into a graphite mold, and vacuum sintered at 1100°C and a sintering pressure of 100 MPa for 3 minutes, then cooled to 800°C and kept at no pressure for 5 minutes to remove the core block stress, thereby preparing a SrTiO3-1wt.% BNNT composite ceramic core block.

[0054] Example 2

[0055] The amount of modified boron nitride nanotubes was changed so that the mass percentage of boron nitride nanotubes in the strontium titanate / boron nitride nanotube composite ceramic core block was 2%, and the rest was the same as in Example 1, to prepare a SrTiO3-2wt.%BNNT composite ceramic core block.

[0056] Example 3

[0057] The amount of modified boron nitride nanotubes was changed so that the mass percentage of boron nitride nanotubes in the strontium titanate / boron nitride nanotube composite ceramic core block was 3%, and the rest was the same as in Example 1, to prepare a SrTiO3-3wt.%BNNT composite ceramic core block.

[0058] Comparative Example

[0059] The SrTiO3 powder was loaded into a graphite mold and vacuum sintered at 1100°C and a sintering pressure of 100 MPa for 3 minutes, then cooled to 800°C and kept without pressure for 5 minutes to remove the core block stress, thereby preparing an undoped SrTiO3 single-phase ceramic core block.

[0060] Performance Testing

[0061] Figure 1 This is a scanning electron microscope image of the composite powder obtained by wet mixing of boron nitride nanotubes (BNNTs) modified by hydrothermal reaction with sodium hydroxide solution and strontium titanate powder in Example 1. It can be clearly seen that the BNNTs are uniformly dispersed in the SrTiO3 ceramic powder.

[0062] Figure 2 This is a comparison chart of the thermal conductivity of the SrTiO3-1wt.% BNNT, SrTiO3-2wt.% BNNT, SrTiO3-3wt.% BNNT composite ceramic core blocks prepared in Examples 1-3 respectively and the SrTiO3 single-phase ceramic core blocks prepared in the comparative example. It can be seen that doping 1-3wt.% of BNNT in SrTiO3 ceramics can significantly improve the thermal conductivity of the SrTiO3 ceramic core blocks.

[0063] Figure 3 This is a hardness comparison chart of the SrTiO3 single-phase ceramic core block prepared in the comparative example and the SrTiO3-2wt.% BNNT composite ceramic core block prepared in Example 2. It can be seen that the BNNT with a mass percentage of 2wt.% (volume ratio of about 7vol.%) in the SrTiO3 ceramic can significantly improve the hardness of the SrTiO3 ceramic core block.

[0064] In summary, after adding boron nitride nanotubes into strontium titanate ceramic powder, the thermal conductivity and mechanical properties of the composite ceramic core block can be significantly enhanced.

[0065] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A strontium titanate / boron nitride nanotube composite ceramic core block, characterized in that: The composite ceramic core block is prepared by using strontium titanate and boron nitride nanotubes. The mass percentage of boron nitride nanotubes in the strontium titanate / boron nitride nanotube composite ceramic core block is 0.1% to 3%.

2. The strontium titanate / boron nitride nanotube composite ceramic core block according to claim 1, characterized in that: The boron nitride nanotubes have an average diameter of 50 nm and a length of 10-20 μm; the strontium titanate has an average particle size of 200 nm.

3. A method for preparing a strontium titanate / boron nitride nanotube composite ceramic core block as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: S1: functionalizing the boron nitride nanotubes with an alkaline solution to obtain surface-modified boron nitride nanotubes; S2: Dispersing strontium titanate uniformly in anhydrous ethanol to obtain strontium titanate slurry, and stirring continuously; S3: evenly dispersing the surface-modified boron nitride nanotubes in anhydrous ethanol to obtain a surface-modified boron nitride nanotube slurry, and adding the slurry to the strontium titanate slurry to obtain a strontium titanate / boron nitride nanotube slurry, and continuously stirring; S4: heating and stirring the strontium titanate / boron nitride nanotube slurry to obtain a strontium titanate / boron nitride nanotube composite powder; S5: pressing and sintering the strontium titanate / boron nitride nanotube composite powder into a core block embryo to obtain a strontium titanate / boron nitride nanotube composite ceramic core block.

4. The method for preparing a strontium titanate / boron nitride nanotube composite ceramic core block according to claim 3, characterized in that: In step S1, the alkaline solution includes a sodium hydroxide solution, the concentration of the sodium hydroxide is 5-6 mol / L, and the usage ratio of the boron nitride nanotubes to the sodium hydroxide solution is (10-100 mg):15 mL.

5. The method for preparing a strontium titanate / boron nitride nanotube composite ceramic core block according to claim 4, characterized in that: In step S1, the specific process of the functionalization is: ultrasonically disperse the boron nitride nanotubes in a sodium hydroxide solution, place them in a polytetrafluoroethylene-lined hydrothermal reactor, react at a temperature of 110-180°C for 12-24 hours, centrifuge and wash until neutral, and dry them at 70-90°C for 12-24 hours.

6. The method for preparing a strontium titanate / boron nitride nanotube composite ceramic core block according to claim 3, characterized in that: In step S2, the stirring is carried out by an overhead electric stirrer at a stirring speed of 300 to 1200 rpm.

7. The method for preparing a strontium titanate / boron nitride nanotube composite ceramic core block according to claim 3, characterized in that: In step S3, the dispersion includes ultrasonic dispersion, the ultrasonic dispersion time is 2-3h, and during the ultrasonic dispersion process, the temperature of the surface modified boron nitride nanotube slurry is not higher than 60°C; the surface modified boron nitride nanotube slurry is dripped into the strontium titanate slurry at a rate of 1-5ml per second.

8. The method for preparing a strontium titanate / boron nitride nanotube composite ceramic core block according to claim 3, characterized in that: In step S4, the heating and stirring are performed until the solvent in the strontium titanate / boron nitride nanotube slurry is dried. Before the strontium titanate / boron nitride nanotube composite powder is obtained, the strontium titanate-boron nitride nanotube slurry mixed with the solvent is placed in a vacuum drying oven for further drying. The drying temperature of the vacuum drying oven is 80-120°C and the drying time is 20-30 hours.

9. The method for preparing a strontium titanate / boron nitride nanotube composite ceramic core block according to claim 3, characterized in that: In step S5, the sintering method includes spark plasma sintering, the sintering temperature is 1050-1200°C, the sintering pressure is 80-100 MPa, and the sintering temperature is maintained for 3-5 minutes after reaching the sintering temperature; after the insulation is completed, the temperature is reduced to 700-900°C and the pressure is removed and maintained for 5-10 minutes.

10. An application of a strontium titanate / boron nitride nanotube composite ceramic core block as claimed in claim 1, characterized in that: Including the application of high power radioisotope heat source battery core blocks.

Citation Information

Patent Citations

  • Preparation method of boron nitride nanotube toughened titanium carbide neutron absorption ceramic

    CN109020587A

  • Modified organic silicon composite material as well as preparation method and application thereof

    CN113583449A

Cited By

  • Application of paintable high-conductivity flexible composite material

    CN119626634A